PARADIGMA DOMINASI VIS AS VIS HARMONI ATAS ALAM: STUDI KRITIS PERSPEKTIF TEO-EKOLOGI ISLAM - Mudin, Moh. Isom; Saputri, Nafiatus; Hedi Ouannes, Mohamed (Academic Journal of Islamic Principles and Philosophy, 2025)
This article discusses academic issues related to the model of human domination over nature and its environmental impact, particularly in the context of the worldview of Islam. This model has led to rapid and severe environmental damage. The study employs a critical analysis method of textual and written materials, with an emphasis on understanding key Islamic concepts related to the relationship between humans and nature. The analysis aims to describe the dominant worldviews, such as anthropocentrism and the holistic ecological worldview within Islam. The research findings indicate a paradigm shift, transitioning from an organic and spiritual view of nature before 1500 to a mechanistic vision that seeks to control nature thereafter. In the context of Islamic ecology, nature is considered a comprehensive unity and not merely an exploitable object. This article fills a gap in previous research by focusing on the Islamic perspective on nature. We connect this perspective with predominantly Muslim countries' current practices and environmental policies. Furthermore, we compare the Islamic perspective with other paradigms such as ecocentrism and biocentrism, offering policy recommendations to integrate the Islamic perspective on nature into environmental conservation efforts. Islam offers a distinct worldview that emphasizes the relationship between humans and nature and their responsibility to preserve it as an act of obedience to the Creator. Therefore, Islam has the potential to provide solutions to current ecological challenges.